2016
DOI: 10.1002/2015wr018198
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying the importance of spatial resolution and other factors through global sensitivity analysis of a flood inundation model

Abstract: Where high-resolution topographic data are available, modelers are faced with the decision of whether it is better to spend computational resource on resolving topography at finer resolutions or on running more simulations to account for various uncertain input factors (e.g., model parameters). In this paper we apply global sensitivity analysis to explore how influential the choice of spatial resolution is when compared to uncertainties in the Manning's friction coefficient parameters, the inflow hydrograph, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
81
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 116 publications
(86 citation statements)
references
References 106 publications
5
81
0
Order By: Relevance
“…Input hydrographs are one of the most important parameters that can have a significant impact on the hydraulic flood modelling results [23]. Savage et al [23] have shown that input hydrographs have a significant influence on modelling results, especially during rising limb of the hydrograph.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Input hydrographs are one of the most important parameters that can have a significant impact on the hydraulic flood modelling results [23]. Savage et al [23] have shown that input hydrographs have a significant influence on modelling results, especially during rising limb of the hydrograph.…”
Section: Introductionmentioning
confidence: 99%
“…Input hydrographs are one of the most important parameters that can have a significant impact on the hydraulic flood modelling results [23]. Savage et al [23] have shown that input hydrographs have a significant influence on modelling results, especially during rising limb of the hydrograph. During peak discharge, the channel friction parameter has the largest impact, whereas during the recession part of the hydrograph, the floodplain friction parameter plays an important role.…”
Section: Introductionmentioning
confidence: 99%
“…different probability distribution functions, imprecise probabilities or process representations (e.g. Hall, 2006;Baroni and Tarantola, 2014;Savage et al, 2016) or that allow us to explore the impact of distributions that are practically unconstrained due to a lack of observations (e.g. Prudhomme et al, 2010;Singh et al, 2014;Almeida et al, 2016).…”
Section: Assessing Whether a Decision Is Robust To The Chosen Assumptmentioning
confidence: 99%
“…However, in all cases it will be good practice to assess the sensitivity of the outcomes to a range of feasible assumptions (e.g. Saltelli, 2002;Tang et al, 2007;Saltelli et al, 2008;Pianosi et al, 2015;Savage et al, 2016).…”
mentioning
confidence: 99%
“…(Sobol, 1993) to identify the relevant system processes for groundwater flow and reactive transport represented in different model structures. Savage et al (2016) applied GSA to identify the dominant controls in the calculation of flood inundation, to assess whether a high spatial resolution of the flood inundation model or the model parametrization is dominating the simulation. The mentioned studies illustrate the use of GSA with discrete and complex model inputs.…”
Section: Introductionmentioning
confidence: 99%